PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020-2024) - Making, Klotilde Elian N. (SINERGI : Jurnal Riset Ilmiah, 2025)
The purpose of this study is: 1) To determine the positive and significant influence between company size and company value, 2) To determine the positive and significant influence between profitability and company value, 3) To determine the positive and significant influence between dividend policy and company value. The sample used are manufacturing company listed on the Indonesia Stock Exchange for the 2020-2024 period as many as 24 companies. The data analysis technique used is multiple linear regression. The results of the study show that: 1) Company size has a positive effect on company value, proven. This is indicated by a regression coefficient of -0,262 and a sig value of 0,038 < 0,05. 2) Profitability has a positive effect on company value, not proven. This is indicated by a regression coefficient of 0,669 and a sig value 0,759 > 0,05. 3) Dividend policy has a positive effect on company value, not proven. This is indicated by a regression coefficient of -0,009 and a sig value 0,610 > 0,05.